2001
DOI: 10.1108/eum0000000005459
|View full text |Cite
|
Sign up to set email alerts
|

Graduates into sales – employer, student and university perspectives

Abstract: Graduate employers are faced with the challenges posed by an increasingly complex graduate labour market as well as increasing graduate recruitment and retention problems. In the light of these issues this paper considers graduate attitudes and behaviour towards sales jobs, and employers’ response to recruitment of graduates into sales. Results from interviews with key UK graduate employers and a survey of final year students at a Northern Business School show that there is a need for employers to enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…These reasons are (a) acceleration of poor quality deterioration (b) quality deterioration in key skill areas (c) production of poor quality graduates by poor quality staff. Similar findings have been identified by Harvey L. [5] and [4] -research done in Birmingham, Duoc and Metzger [3] -research conducted on quality of business graduates in Vietnamese institutions, Murray and Robinson [13], Nabi and Bagley [14] -research covered the graduates in the UK. All these research concluded that graduates should develop a range of soft skills including business skills, general and transferable skills, self and personal skills, attitudes, in order to increase their employability in the potential labour market as well as to meet the employer expectations.…”
Section: Literature Reviwesupporting
confidence: 84%
“…These reasons are (a) acceleration of poor quality deterioration (b) quality deterioration in key skill areas (c) production of poor quality graduates by poor quality staff. Similar findings have been identified by Harvey L. [5] and [4] -research done in Birmingham, Duoc and Metzger [3] -research conducted on quality of business graduates in Vietnamese institutions, Murray and Robinson [13], Nabi and Bagley [14] -research covered the graduates in the UK. All these research concluded that graduates should develop a range of soft skills including business skills, general and transferable skills, self and personal skills, attitudes, in order to increase their employability in the potential labour market as well as to meet the employer expectations.…”
Section: Literature Reviwesupporting
confidence: 84%
“…In relation to the skills examined, Mihail (2006) used 22 areas of skills from Murray and Robinson (2001) to investigate the most important benefits attained by students from the industrial training at Greek universities. These areas of skills were extracted from the three main categories of skills which are academic, enterprise and personal development skills.…”
Section: Skills Acquisitionmentioning
confidence: 99%
“…Since a large percentage of marketing students will start their professional careers after graduation in sales positions (Murray & Robinson, 2001), it is possible to influence or at least identify these students as they make their way through a marketing/sales major or minor.…”
Section: Discussionmentioning
confidence: 99%